ASSOCIATION OF THE PAX7’S 31-BP-INDEL POLYMORPHISM WITH SOME MEAT QUALITY TRAITS IN VIETNAMESE NOI CHICKENS AT 91 DAYS OLD - N.T.D. Thuy; N.T.H. Tuoi; N.T. Giang; H.T.P. Loan; T.T. Hoan; N.T. N. Linh; D.V.A. Khoa (Journal of Animal and Plant Sciences, 2021)
Pax7 is important for the activation of satellite cells during myogenesis as well as the development of muscle, which can relate to meat quality traits. However, no evidence for this has been reported. In this study, an investigation into the relation between the 31 bp-indel polymorphism of the Pax7 and meat traits was conducted on 355 native Noi broilers. Thus, firstly, three genotypes (EE, EF and FF with frequencies of 0.12, 0.70 and 0.18, respectively) of Noi chickens at this locus were detected based on distinct PCR fragments of agarose gel. Secondly, some traits of meat quality and chemical composition were evaluated on the chicken population. Finally, a correlation analysis among genotypes and the observed traits showed that the 31bp-indel site was significantly associated with (i) the yellowness (b*) at 3h and 48h post-mortem of beast meat, (ii) the redness (a*) at 3h and the yellowness (b*) at 48h post-mortem of thigh meat, and (iii) cooking loss at 48h post-mortem of thigh meat (p≤0.05). Furthermore, statistically significant differences in the interaction among genotypes and sex for colour traits and pH of breast or thigh meat at different time points as well as the crude protein of breast meat were found (p≤0.05). In conclusion, the 31 bp-indel of PAX7 gene could be considered as a theoretical basis for further research on the application of the PAX7 gene in Noi chicken breeding programs.
Keywords: genetic variation; meat; Noi chickens; quality traits